Peranan Pemerintah Desa dalam Pencegahan Stunting Di Desa Kencana Kecamatan Balai Jaya Tahun 2022 - Puji Lestari; Fitri Pralistami; Dewi Ratna; Siti Hamijah; Reni Agustina Harahap (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Based on the 2019 Basic Health Research data, the stunting rate in Indonesia is 27.67%. According to WHO, a public health problem is considered chronic when the prevalence of stunting exceeds 20%. 6 of 2014, villages are required to develop programs or activities related to stunting prevention. So in this Real Work Lecture activity, the researcher wanted to know how the role of the Kencana village government in stunting prevention was, so the researchers conducted research on the Role of the Village Government in Preventing Stunting in Kencana Village, Balai Jaya District in 2022. The technique for selecting research subjects was carried out purposively which obtained several The subjects were Kencana Village Apparatus, mothers with toddlers, and Village Midwives. Data collection techniques were carried out by direct interviews with informants using interview guidelines. From the results of our research, it can be concluded that the role of the village government in preventing stunting, especially health, has been carried out well. Both the allocation of funds and the actions and ideas made by the Kencana village government have made the Kencana village avoid stunting, the village government's efforts such as providing additional food, sweeping kids, immunization of children and providing additional food to pregnant women.